The Effects of Using E-Leaflet and Lecture Methods on Maternal Knowledge Regarding Stunting Prevention in Toddlers - Ariani, Dini; Septiani, Hani; Srinayanti, Yanti (Genius Journal, 2024)
Objective: The objective of this research is to assess the impact of utilizing e-leaflets and lecture methods on the knowledge of mothers with toddlers in stunting prevention. Method: A quasi-experimental approach with a pre-test/post-test two-group research design was employed. The participants in this study consisted of 40 mothers of toddlers, and data collection was done using a questionnaire. Result: The significance value (2-tailed) was found to be 0.0043, which is less than 0.05. This leads to the conclusion that there is a significant disparity in knowledge before and after providing the e-leaflet and lecture. Conclusion: The research highlights a significant disparity in knowledge acquisition following the distribution of e-leaflets and lectures among mothers of toddlers.